Comparative Whole-Genomic Analysis of an Ancient L2 Lineage Mycobacterium tuberculosis Reveals a Novel Phylogenetic Clade and Common Genetic Determinants of Hypervirulent Strains - Rajwani, Rahim; Yam, Wing Cheong; Zhang, Ying; Kang, Yu; Wong, Barry Kin Chung; Leung, Kenneth Siu Sing; Tam, Kingsley King Gee; Tulu, Ketema Tafess; Zhu, Li; Siu, Gilman Kit Hang (Frontiers in Cellular and Infection Microbiology, 2018)
Background: Development of improved therapeutics against tuberculosis (TB) is hindered by an inadequate understanding of the relationship between disease severity and genetic diversity of its causative agent, Mycobacterium tuberculosis. We previously isolated a hypervirulent M. tuberculosis strain H112 from an HIV-negative patient with an aggressive disease progression from pulmonary TB to tuberculous meningitis – the most severe manifestation of tuberculosis. Human macrophage challenge experiment demonstrated that the strain H112 exhibited significantly better intracellular survivability and induced lower level of TNF-α than the reference virulent strain H37Rv and other 123 clinical isolates. Aim: The present study aimed to identify the potential genetic determinants of mycobacterial virulence that were common to strain H112 and hypervirulent M.tuberculosis strains of the same phylogenetic clade isolated in other global regions. Methods: A low-virulent M.tuberculosis strain H54 which belonged to the same phylogenetic lineage (L2) as strain H112 was selected from a collection of 115 clinical isolates. Both H112 and H54 were whole-genome-sequenced using PacBio sequencing technology. A comparative genomics approach was adopted to identify mutations present in strain H112 but absent in strain H54. Subsequently, an extensive phylogenetic analysis was conducted by including all publically available M.tuberculosis genomes. Single-nucleotide-polymorphisms (SNPs) and structural variations (SVs) common to hypervirulent strains in the global collection of genomes were considered as potential genetic determinants of hypervirulence. Results: Sequencing data revealed that both H112 and H54 were identified as members of the same sub-lineage L2.2.1. After excluding the lineage-related mutations shared between H112 and H54, we analyzed the phylogenetic relatedness of H112 with global collection of M.tuberculosis genomes (n=4,338), and identified a novel phylogenetic clade in which four hypervirulent strains isolated from geographically diverse regions were clustered together. All hypervirulent strains in the clade shared 12 SNPs and 5 SVs with H112, including those affecting key virulence-associated loci, notably, a deleterious SNP (rv0178 p. D150E) within mce1 operon and an intergenic deletion (854259_ 854261delCC) in close-proximity to phoP. Conclusion: The present study identified common genetic factors in a novel phylogenetic clade of hypervirulent M.tuberculosis. The causative role of these mutations in mycobacterial virulence should be validated in the future study.